Nevett, Lisa, Ancient Greek Housing. - Bintliff, John (Journal of Greek Archaeology, 2025)
Lisa Nevett has established herself as perhaps the foremost current expert in ancient Greek housing, both in the homeland and the Greek colonial world, since the publication of her thesis on this topic in the 1990’s (Nevett 1999). She has taken her scholarship further with the significant reopening of excavations at a key ancient planned city at Olynthus in Northern Greece.